Optimal maintenance for a waste-to-energy plant using DEMATEL : A case study - Igodo, Alassani; Shamsuzzoha, Ahm; Ndzibah, Emmanuel; Shamsuzzaman, Mohammad (Springer, 2023)
Waste-to-energy (WtE) plants are complex systems that requiring different types of maintenance to be reliable and available in functionality. The inadequacies of WtE plant lifetime maintenance may increase the production costs and negatively affect the competitiveness and the availability of WtE plants. To keep the efficiency of all the plant systems high and operating as expected during their lifetime, it is important to maintain them. This study focuses on the maintenance of WtE plants by analyzing the operating procedures at a case company. In the study, a multi-criterion decision-making method (MCDM) named Decision-Making Trial and Evaluation Laboratory (DEMATEL) is used to evaluate the weight and rank of twelve identified criteria for spare parts of the case WtE company. The empirical part of this study consists of a qualitative study, where data were collected from an open-ended questionnaire survey and case company data from existing documents. The respondents' rate from the questionnaire survey was 20%. Key findings from the study show that human, economic, equipment and tool related, management, and environmental factors have an important impact on the effectiveness of the maintenance and availability of the WtE plant. The study also shows that quality, lead time, price, and the severity of spare part failure are the key criteria to consider when selecting spare parts for the WtE plant. The study recommends several initiatives to improve the availability of WtE plant and spare parts which will help to reduce the costs of maintenance as well as mitigate the risks related to the maintenance.
Keywords: Corrective maintenance; DEMATEL MCDM; Maintenance program; Maintenance strategy; Multi-criteria decision-making (MCDM); Municipal solid waste (MSW); Optimization; Waste-to-energy (WtE); fi=Tuotantotalous|en=Industrial Management|